2015
DOI: 10.1242/dev.109454
|View full text |Cite
|
Sign up to set email alerts
|

Geminin deletion increases the number of fetal hematopoietic stem cells by affecting the expression of key transcription factors

Abstract: Balancing stem cell self-renewal and initiation of lineage specification programs is essential for the development and homeostasis of the hematopoietic system. We have specifically ablated geminin in the developing murine hematopoietic system and observed profound defects in the generation of mature blood cells, leading to embryonic lethality. Hematopoietic stem cells (HSCs) accumulated in the fetal liver following geminin ablation, while committed progenitors were reduced. Genome-wide transcriptome analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 78 publications
4
28
0
4
Order By: Relevance
“…We showed that Geminin antagonizes both GemC1 and McIdas, inhibiting their transactivation potential. Geminin has been shown to be expressed in proliferating cells and to regulate proliferation–differentiation decisions . Consistently, we observed the expression of Geminin in proliferating MTECs, which is decreased as cells progress toward differentiation, in parallel with the induction of GemC1, McIdas and FoxJ1.…”
Section: Discussionsupporting
confidence: 87%
“…We showed that Geminin antagonizes both GemC1 and McIdas, inhibiting their transactivation potential. Geminin has been shown to be expressed in proliferating cells and to regulate proliferation–differentiation decisions . Consistently, we observed the expression of Geminin in proliferating MTECs, which is decreased as cells progress toward differentiation, in parallel with the induction of GemC1, McIdas and FoxJ1.…”
Section: Discussionsupporting
confidence: 87%
“…Increased Geminin expression has also been reported in many cancer cell types and the elevated expression of GEMC1 or Multicilin could provide an alternative means for facilitating DNA replication in this context (Kapoor, ). In addition, we have observed that the overexpression of Geminin that also has transcriptional roles, including the inhibition of Multicilin, inhibits GEMC1‐mediated activation of target genes (Fig D) (Yellajoshyula et al , ; Ma et al , ; Karamitros et al , ), suggesting the existence of reciprocal regulatory mechanisms between GEMC1 and Geminin.…”
Section: Discussionmentioning
confidence: 93%
“…It was previously shown that GemC1 forms heterodimers with McIdas and Geminin, whereas Geminin acts antagonistically to GemC1 in the regulation of transcriptional activation of key transcription factors for multiciliogenesis (Arbi et al, 2016;Caillat et al, 2013;Caillat et al, 2015;Kyrousi et al, 2015;Patmanidi et al, 2017;Terré et al, 2016). As Geminin was previously shown to be implicated in stem cell self-renewal and differentiating decisions (Karamitros et al, 2015;Spella et al, 2011), antagonistic roles for Geminin and GemC1 in determining the ependymal cell lineage are likely. Although the human genetic findings we provide will require further validation by sequencing other congenital hydrocephalus patients, the fact that ependymogenesis in mice and humans shares many common characteristics (Coletti et al, 2018;Pressler & Auvin, 2013), suggests that the mechanism defined here in mice may be operative in some forms of human congenital hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%